Demographic profile of participants and the types of rural enterprises in Zululand District Municipality, KwaZulu Natal. - Zipho Chamane (PhD Candidate) (African Journal of Hospitality, Tourism and Leisure, 2018)
Rural enterprises have an important role to play in rural development because of their potential in inter alia, providing employment, alleviating poverty and achieving food security. These enterprises include tourism related enterprises. The article forms part of the larger study which seeks to assess the contribution of rural enterprises on rural development and itsupports the notion that tourism can indeed contribute to the stimulation of rural enterprises which can lead to enhanced rural development and poverty alleviation This article however, only reports on the demographic data of the owners and managers of the rural enterprises and their types of enterprises in Zululand District Municipality. A snowball method was used, and twenty rural enterprises participated in the study. A mixed method approach which thus included qualitative and quantitative methods was used to collect data from the participants. Data was collected using a structured questionnaire in order to determine the demographic profiles of the participants and the types of enterprises they tended to own. The results revealed that gender had no influence in owning the rural enterprise. The majority of enterprise owners were above the age of 46 years. There were more married people in the sample who were the owners of enterprises. Most enterprise owners had at least secondary level education and were from large households. The participants had no other incomes except that which they obtained from their respective enterprises. There were more farming than non-farming enterprises. Participants opted the business they are doing because they simply need to survive and thus wanted to earn a living out of it. They started their rural enterprises with a meagre start-up capital of below R1000. In conclusion, in order to contribute significantly to rural development, rural enterprises must be supported by both government and the financial sector so that the problem of poverty can be mitigated effectively.